Performance-related: Pay and gender wage differences - Mari Kangasniemi; Antti Kauhanen (The Research Institute of the Finnish Economy (ETLA), 2011)
We study the impact of performance-related pay (PRP) on gender wage differences using Finnish linked employer-employee panel data. Controlling for unobserved person and firm effects, we find that bonuses increase women's earnings slightly less than men's, but the economic significance of the difference is negligible. Piece rates and reward rates, however, tend to increase gender wage differentials. Thus, the nature of a performance related pay plan is important for gauging the impact of PRP on gender wage differentials. A comparison with OLS results shows the importance of controlling for unobserved person and firm effects.
Keywords: J16; J33; M52; 330; gender wage differences; performance-related pay; person and firm effects; panel data; Leistungsentgelt; Lohndifferenzierung; Fraueneinkommen; Finnland